Environmental risks in independent industrial activity sander - Jeronimo, Carlos Enrique de Medeiros; Nascimento, Cristian Emilio Montenegro; Sousa, Cacilda Alves de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708880 The present work looked to focus the studies directed on the activities developed by the autonomous sanders in industry assembly city Mossoró-RN, whose main focus was the production assembly and maintenance of equipment. The goal was to identify and analyze the physical agents heat and noise which mainly sanders are exposed, proposing measures to reduce the harmful consequences and possible risks, proposing the implementation of preventive measures applied and engineering industry. Regarding the methodology used was treated for an exploratory field research with quantitative and objective natures or participants. According to what we need, we sought to carefully evaluate several factors, it was possible to make a combination of the performance of this activity to a healthier environment for employees of industrial assembly, by applying checklist and analysis, using specific devices like the decibel meter and thermal stress, thereby collecting information and thereby evaluating the activities of employees to qualify and add effective control measures to minimize or negate the physical damage, aiming to provide a better quality of labor officials who carry this activity in their daily lives.